Envelhecimento e longevidade na modernidade técnica : os desafios do prolongamento da vida - Alves, Cristina Alesxandra do Nascimento (2016)
The ambivalence of human actions on the world and about themselves raises numerous questions about the actual and potential consequences of the changes we are witnessing. Projections of techno science say that we are about to reach an advanced state of mankind, some of them even speaking of an anthropological rupture through technological development. With technically improved and disease free human beings, with an indefinitely long life. The pursuit for longevity is not something new in the human history; on the contrary, over time we can find several examples of how men and women sought to achieve this goal. Nowadays, the search for a longer life's lies mainly in the techno scientific development, their knowledge and increasing manipulation capacity of the human body at the molecular and genetic level. However, the increase in life expectation of a society has demographic, economic and social security consequences as we find ourselves in increasingly older societies. With more retired individuals and probably a smaller portion of the economically active population. Thus, it provides for an overhaul in the way we think not only the relationship of man to his body, life and death. But also the very old age, retirement and even labor market, aiming at solving the problems of suppression of the economically active portion of the population on a more long-lived society. What we propose is to study the impact of technologies applied to the body in order to prolong their youth and to identify and analyze some of the consequences of increased human longevity that we have witnessed today. Instead of being interested in a study of what might be the future of man, we are concerned with the changes that are announced in a concrete way and are already for some time, the interest of researchers in the humanities and who already have consequences and problems in current days. We, therefore, propose to study this theme and give an overview of the body and technical relationship to view more specific aspects of the relationship of modern man with his body, old age and death, and consequently the social and sociological implications.